Sugar-sweetened beverage/snack consumption and its determinants among infant and young children aged 6–23 months in twelve Sub-Saharan African countries: Evidence from 2019–2023 Demographic Health Survey data - Birtukan Gizachew Ayal; Abebe Kassa Geto; Sefineh Fenta Feleke; Ali Yimer; Atitegeb Abera Kidie; Natnael Amare Tesfa; Esuyawkal Mislu; Molla Hailu; Hassen Ahmed Yesuf (PLoS ONE, 2025)
Background Sugar-sweetened beverages or snacks are limited in nutritional value. Excess consumption of sugar-sweetened beverages or snacks in early childhood is associated with inadequate micronutrient intake, being overweight or obese, and developing chronic diseases later in life. There is scarcity of information specific to sugar-sweetened beverages or snacks consumption prevalence and its determinants in Sub-Saharan Africa Countries. This study aimed to determine the pooled prevalence of sugar-sweetened beverage or snack consumption and its determinants among infants and young children aged 6–23 months. Methods A cross-sectional study design was conducted using demographic and health survey data conducted from 2019 to 2023 from twelve Sub-Saharan African countries. A weighted sample of 23,145 children aged 6–23 months was included in the study. Multilevel mixed-effects logistic regression analysis was used to determine the factors associated with the dependent variable. The level of statistical significance was declared with a p-value < 0.05 and an adjusted odds ratio with a 95% confidence interval. Results The pooled prevalence of Sugar-sweetened beverage or snack consumption was 25.40% (95% CI: 24.84% − 25.96%). In multilevel multivariable logistic regression analysis, children aged between 9−11(AOR = 1.95 95% CI: 1.62, 2.35), 12–17(AOR = 2.83; 95% CI: 2.26, 3.54), and 18−23 months (AOR = 3.77;95% CI: 3.07, 4.63), media exposure (AOR = 1.59; 95% CI:1.28, 1.98), children from households with middle (AOR = 1.39; 95% CI: 1.11, 1.73) and rich (AOR = 2.31; 95% CI: 1.87, 2.85) wealth status, post natal checkup (AOR = 1.18; 95%CI:1.05,1.33), maternal ANC visit (AOR = 1.60; 95% CI: 1.15, 2.22), and high community media exposure ((AOR = 2.22;95%CI:1.65,5.81) were positively associated significant factors whereas currently breast feeding children (AOR = 0.70; 95% CI: 0.59,0.82), older age at first birth (AOR = 0.88,95% CI: 0.81, 0.96), presences of more than one under-5 children in the household (AOR = 0.89, 95% CI: 0.80, 0.99), mothers don’t perceive distance to health facility as big problem (AOR = 0.86; 95% CI:0.76, 0.98), and children reside in rural (AOR = 0.83;95%CI:0.68,0.95) were negatively associated with sugar sweetened beverage or snack consumption. Conclusion In this study, one out of four children consumed sugar-sweetened beverages or snacks. Current age of child, current breastfeeding status of child, media exposure, wealth index, maternal age at first birth, post natal checkup, maternal ANC visit, number of under-five children in the household, distance to health facility, place of residence, and community level media exposure were significant factors with sugar-sweetened beverage or snack consumption. Therefore, it is recommended to raise awareness about the health risks of sugar-sweetened beverage and snack consumption, enforce restrictions on their advertisement, strengthen nutrition-focused counseling within maternal and child health services with special attention for older age children, promote breastfeeding, and give special attention to challenges related to health facility accessibility, and support for young mothers.